The Effect of Scientific Approach Based on Portfolio Assessment towards the Learning Outcomes of Civic Education of the Students Grade V Viewed from the Tendency of Observing Objects on Theme 7 SDN 4 Ubung - Agusditya, Putu Handy; Sri Asri, I.G.A.A.; Suara, I Made (Journal of Education Reseach and Evaluation, 2017)
This study is aimed at determining significant differences between the Civics learning outcomes of the students who took a scientific approach based learning with portfolio assessment in terms of concrete objects and students who took a scientific approach based learning with portfolio assessment in terms of abstract objects. This study is a pre-experiment (pre-experimental design) with the design of the study was the Static Group Pretest-Posttest Design. The population in this study was the students of grade V SDN 4 Ubung Denpasar, in the academic year 2014/2015, amounting to 60 people. The samples were taken by using random sampling techniques. The data in the form of the value of Civics learning outcomes were collected with the usual multiple-choice test. The data were analyzed using descriptive statistics and t-test. The results showed that there were differences between the Civics learning outcomes of students who took a scientific approach based learning with portfolio assessment in terms of concrete objects and students who took a scientific approach based on learning through portfolio assessment in terms of abstract objects with t = 2.29, t table with 5% level of significance and db = 58, obtained t table at 2.00. This meant that tobserved > ttable (2.29> 2.00). Based on these results, it could be concluded that the scientific approach based on a portfolio assessment in terms of the object being observed on the theme of the history of civilization of Indonesia influenced the learning outcomes of Civics of the students grade V in SDN 4 Ubung Denpasar.